Measuring the Quality of the General Election Commission Website in Central Jakarta Using the WebQual 4.0 Method - Naufal Brilianto; Ahmad Fauzi; Artika Surniandari; Hilda Rachmi (Universitas Islam Kuantan Singingi, 2024)
This study aims to analyze the application of the Webqual 4.0 method in measuring the quality of the Central Jakarta City General Election Commission (in Indonesia it is abbreviated as KPU) website. This method focuses on three dimensions of usability quality, information quality, and interaction quality. This study uses a quantitative method with primary data. The sample of this study were employees and the general public. The data analysis technique used was multiple linear analysis processed using the SPSS version 26 program. The results of the study showed that the usability variable did not have a significant effect on website quality measurement. The Information Quality variable did not have a significant effect on website quality measurement. And the Interaction Quality variable had a significant effect on website quality measurement.